Convenient chromatography-free access to enantio-pure 6,6’-di-tert-butyl-1,1’- binaphthalene-2,2’-diol- its 3,3’-dibromo, di-tert-butyl and phosphorus derivatives: utility in asymmetric synthesis - Balaraman, Ekambaram; Swamy, K. C. Kumara (Tetrahedron-Asymmetry, 2007)
A simple chromatography-free high-yielding synthesis of the hexane-soluble enantiopure 6,6′-di-tert-butyl-1,1′-binaphthalene-2,2′-diol 3 (6,6′-di-tert-butyl BINOL) using Friedel–Crafts reaction on 1,1′-binaphthalene-2,2′-diol 1 (BINOL) is described. The enantiomeric purity was fully maintained in the reaction. Compound 3 has been used as an entry point for the convenient chromatography-free synthesis of 3,3′,6,6′-tetra-tert-butyl BINOL 4 and 3,3′-dibromo-6,6′-di-tert-butyl BINOL 5. A straightforward route to enantiopure bisphosphites [(6,6′-R2C20H10O2)P]2[O2C20H10-6,6′-R2] [R = H 15, t-Bu 16] by simply reacting phosphorochloridite (6,6′-R2C20H10O2)PCl [R = H 20, t-Bu 6] with metallic sodium is highlighted. The identity of 15 and 16 as their selenium-oxidized products 17 and 18 (at phosphorus center) is confirmed by X-ray crystallography (17 in the enantiopure form and 18 as racemate). Various enantiopure phosphoramidites of the modified BINOL have been synthesized. It is established that even when the phosphoramidites derived from the unsusbstituted BINOL 1 fail to give an appreciable optical induction in the asymmetric reduction of acetophenone/phenacyl chloride, those derived from 3 do induce moderate chiral induction (up to 30% ee in the case for acetophenone and 43% ee in the case of phenacyl chloride), thus leaving scope for further improvement in ee for related reactions.

Cyclodiphosph(III)azane chemistry – ylides from the reaction of [(RNH)P-N(t-Bu)]2 [R = t-Bu, i-Pr] with dimethyl maleate and chiral ansa-type derivatives from reaction of [ClP-N(t-Bu)]2 with a substituted BINOL - Swamy, K.C. Kumara; Gangadhararao, G.; Srinivas, Venu; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Chakravarty, Manab (Inorganica Chimica Acta, 2011)
Use of a simple inorganic ring system with the cyclodiphosph(III)azane skeleton [e.g. [(RNH)P-N(t-Bu)]2 [R = t-Bu (7), i-Pr (8)] to probe some of the intermediates proposed in phosphine mediated organic reactions is highlighted. Thus the reaction of 7–8 with the allenylphosphine oxide Ph2P(O)C(Ph)double bond; length as m-dashCdouble bond; length as m-dashCH2 (9) affords the phosphinimines [(RNH)P(μ-N-t-Bu)2P(double bond; length as m-dashN-R)-C(double bond; length as m-dashCH2)CH(Ph)-P(O)Ph2] [R = t-Bu (10), i-Pr (11)], while a similar reaction of 7–8 with dimethyl maleate (or dimethyl fumarate) affords the ylides [(RNH)P(μ-N-t-Bu)2P(NH-R)double bond; length as m-dashC(CO2Me)-CH2(CO2Me) [R = t-Bu (18), i-Pr (19)]. The implication of such reactions on phosphine mediated organic transformations including Morita–Baylis–Hillman reaction is mentioned. In a rather rare type of situation, an unusually long phosphoryl (Pdouble bond; length as m-dashO) bond [1.538 (5) Å] as revealed the X-ray structure of {(R)-6,6′-(t-Bu)2-1,1′-(C10H5)2-2,2′-O2-}{P(O)(N-t-Bu)2-P(Se)} (27) is rationalized by means of crystallographic disorder in packing after comparing the data with that in the literature and {1,1′-(C10H6)2-2,2′-O2}{P(Se)(N-t-Bu)2-P(Se)} (29). X-ray structures of the new compounds 10–11, 18–19, 27 and 29 are discussed. Compound 10 crystallizes in the chiral space group Pca2(1) with (S)-chirality at the carbon center [–C(double bond; length as m-dashCH2)CH(Ph)-P] suggesting a case of spontaneous resolution through crystallization.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

Cobalt-catalyzed bis-alkynylation of amides via double C–H bond activation - Landge, Vinod Gokulkrishna; Jaiswal, Garima; Balaraman, Ekambaram (Organic Letters, 2016)
The first example of cobalt-catalyzed selective bis-alkynylation of amides via double C–H bond activation with the directing assistance of a removable bidentate auxiliary is reported. The developed alkynylation strategy is simple, efficient, and tolerant of various functional groups including ether, amine, halides, and heterocyclic motifs. The reaction can be scaled up under mild conditions.

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

Cobalt-based metal complexes prevent repeat tau aggregation and nontoxic to neuronal cells - Gorantla, V. Nalini; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease (AD) is a fatal neurodegenerative disorder with an alarming increase in the death rate every year. AD is characterised by an aberrant accumulation of proteins in the form of aggregates. The axonal microtubule-associated protein Tau and arnyloid-beta undergo structural transition to beta-sheet rich structure and form aggregates in neuronal soma as well as in the extracellular region. The loss of Tau from microtubules leads to the disintegration of axon and causing neuronal degeneration. This led to the development of effective drugs against AD, to prevent Tau aggregation. Here, we synthesized and screen metal-based complexes to prevent Tau protein aggregation. ThS fluorescence and TEM suggested the role of synthetic cobalt complexes in inhibiting Tau aggregation. CD spectroscopy showed that these complexes prevented conformational changes in Tau to beta-sheet. CBMCs were not toxic at lower concentrations and formed non-toxic Tau species. L1 and L2 prevented membrane leakage: whereas, higher concentrations of L3 caused membrane leakage as observed by LDH release assay. The overall results indicate the synthetic cobalt complexes to be a promising molecule against AD. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cobalt-based metals; Tau Aggregation; Tau inhibition; Tau toxicity

Convenient semihydrogenation of azoarenes to hydrazoarenes using H-2 - Sahoo, Manoj K.; Sivakumar, Ganesan; Jadhav, Sanjay; Shaikh, Samrin; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2021)
The high atom-economical and eco-benign nature of hydrogenation reactions make them much more superior to conventional reduction and transfer hydrogenation. Herein, a convenient and highly selective hydrogenation reaction of azoarenes using molecular hydrogen to access diverse hydrazoarenes is reported. The present catalytic method is general and operationally simple, and it operates under exceedingly mild conditions (room temperature and 1 atm of hydrogen pressure). The reusability of catalysts used in this method is also successfully demonstrated.